Instanciações de gêneros da família dos relatórios na perspectiva sistêmico-funcional em livro didático de ciências da natureza - Silva, Maria Cecilia de Castro da (2023)
This research aims to investigate the experiential linguistic resources involved in the production of text genres from the reports family in natural sciences textbooks for the 6th year of elementary school. For this, are used theoretical-methodological bases of Systemic-Functional Linguistics (HALLIDAY; MATTHIESSEN, 2014) and the text genre perspective outlined from the assumptions of this theory (MARTIN; ROSE, 2008). The texts are analyzed based on the most relevant linguistic systems, according to previous studies, for the realization of reports, the lexical-grammatical system of transitivity (HALLIDAY; MATTHIESSEN, 2014), and the subsystems of taxonomic relations and sequences of activities of the discursive system of IDEATION (MARTIN; ROSE 2007). The analysis’ universe consists of the 6th-grade textbook of the “Teláris – Sciences” collection by Fernando Gewandsznajder and Helena Pacca, chosen for being the most distributed by the Programa Nacional do Livro e do Material Didático (National Textbook Program) (PNLD) in the triennium 2017-2019. The analysis corpus is composed of 16 texts from Unit 2 – “Life: interaction with the environment”, selected based on the following criteria: 1) having verbal language as constitutive; 2) having an authorial voice and not being fragmented and 3) having the potential to instantiate genres from the reports’ family, that is, present resources that typify genres: generalized participants, substantial relational processes, present tense, descriptive, factual and precise mode, resources to define, classify, compare and contrast and technical vocabulary (MARTIN; ROSE, 2008; DEREWIANKA, 1990). Through the corpus linguistic analysis, 20 reports’ instantiations were identified, among them 3 instantiations of descriptive reports, 7 instantiations of classificatory reports and 10 instantiations of compositional reports. Altogether, the most recurrent phases in all these genres were: definition, function, composition and location. For the realization of these phases and the socio-communicative purpose of the instantiated genres, the most used linguistic resources in the transitivity system were intensive identifying relational clauses, possessive attributive relational clauses and circumstantial attributive relational clauses, in addition to transformative material clauses. In the discursive system of IDEATION predominated taxonomic relations of repetition, part and whole and activities that do not form sequences of activities, performed by relational and material clauses. Based on these data, it was possible to conclude that, in the context of the analyzed corpus, the content is organized based on taxonomies of composition and the description of the components is based on the role they play in the composition of the whole and in relation to the coparts.